2020
DOI: 10.3390/ijerph17186878
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Change during COVID-19 Confinement

Abstract: Background: The lockdown and social distancing caused by COVID-19 may influence common health behavior. The unprecedent worldwide confinement, in which Spain has been one of the most affected—with severe rules governing confinement—may have changed physical activity (PA) and sedentary habits due to prolonged stays at home. Purpose: The aim of this study is to evaluate how self-reported PA and sedentary time (ST) have changed during confinement in the Spanish population. Methods: 3800 healthy adults (age 18–64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
391
20
32

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(496 citation statements)
references
References 23 publications
53
391
20
32
Order By: Relevance
“…Another interesting finding from our review is that, generally, those that were sufficiently active before the confinement (i.e., achieving current minimum recommendations for adults of at least 150 min per week of MVPA; U.S. Department of Health Human Services, 2018 ), were also sufficiently active during the lockdown, despite the reduction in PA levels. This finding, which has been reported also in adults (Castañeda-Babarro et al, 2020 ), could suggest that achieving the recommendations on MVPA help in creating a stronger habit of being physically active, which seemed not to be affected to a large extent by the confinements imposed due to COVID-19.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another interesting finding from our review is that, generally, those that were sufficiently active before the confinement (i.e., achieving current minimum recommendations for adults of at least 150 min per week of MVPA; U.S. Department of Health Human Services, 2018 ), were also sufficiently active during the lockdown, despite the reduction in PA levels. This finding, which has been reported also in adults (Castañeda-Babarro et al, 2020 ), could suggest that achieving the recommendations on MVPA help in creating a stronger habit of being physically active, which seemed not to be affected to a large extent by the confinements imposed due to COVID-19.…”
Section: Discussionsupporting
confidence: 69%
“…These results are in line with the findings from previous studies in both adults and children. Castañeda-Babarro et al ( 2020 ) reported significant decreases in self-reported vigorous PA and walking time of 16.8 and 58.2%, respectively; whereas time spent in sedentary behavior increased during the confinement in Spain. The student group (from children to university students) showed the highest decrease in moderate, vigorous, and waking activities.…”
Section: Discussionmentioning
confidence: 98%
“…In Spain, outdoor activity outside the home was strictly restricted during lockdown, including for PA. Other research reported less time of PA and increased sedentary lifestyle during lockdown in adults in Spain [ 14 ] and in other countries [ 36 ]. In countries with less restrictive confinement measures, which allowed going out of the home to practice PA in open air, an increase in PA has been reported, but also increased time dedicated to sedentary activities, with a negative impact on perceived health [ 16 ].…”
Section: Discussionmentioning
confidence: 98%
“…A number of authors have reported changes in food habits during confinement in several countries [ 8 , 9 , 10 , 11 ] and in different age groups [ 9 , 12 , 13 ]. Changes in PA and quality of sleep associated with confinement have been reported as well [ 14 , 15 , 16 , 17 ]. All those changes in lifestyles can influence the evolution of chronic diseases and risk factors in many people [ 12 , 13 , 16 , 18 , 19 ] with a negative health impact.…”
Section: Introductionmentioning
confidence: 99%
“…The Director General of the World Health Organisation declared COVID-19 a global pandemic on 11 March 2020, which resulted in significant movement restrictions globally and within nations, and this crisis has impacted adults’ ability to engage in the recommended levels of PA and exercise. Some international surveys were conducted early on during the COVID-19 pandemic to investigate the effect of the lockdowns on self-reported PA levels [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. These studies have indicated significant declines in self-reported physical activity levels during COVID-19 restrictions compared to before.…”
Section: Introductionmentioning
confidence: 99%